2016
DOI: 10.1016/j.cub.2015.11.059
|View full text |Cite
|
Sign up to set email alerts
|

The Compact Body Plan of Tardigrades Evolved by the Loss of a Large Body Region

Abstract: The superphylum Panarthropoda (Arthropoda, Onychophora, and Tardigrada) exhibits a remarkable diversity of segment morphologies, enabling these animals to occupy diverse ecological niches. The molecular identities of these segments are specified by Hox genes and other axis patterning genes during development [1, 2]. Comparisons of molecular segment identities between arthropod and onychophoran species have yielded important insights into the origins and diversification of their body plans [3-9]. However, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 45 publications
(72 reference statements)
5
108
0
Order By: Relevance
“…Tardigrada, also known as water bears, is a monophyletic group of microscopic invertebrates characterized by a body consisting of five segments (Mayer, Kauschke, Rüdiger, & Stevenson, ; Smith et al, ), four of which carry lobopodous walking appendages, and an aquatic or semi‐terrestrial lifestyle (Nelson, Guidetti, & Rebecchi, ). Together with their closest relatives, the Onychophora (velvet worms) and Arthropoda (invertebrates with articulated appendages), they represent a clade of legged ecdysozoans (molting animals) called Panarthropoda (Rota‐Stabelli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tardigrada, also known as water bears, is a monophyletic group of microscopic invertebrates characterized by a body consisting of five segments (Mayer, Kauschke, Rüdiger, & Stevenson, ; Smith et al, ), four of which carry lobopodous walking appendages, and an aquatic or semi‐terrestrial lifestyle (Nelson, Guidetti, & Rebecchi, ). Together with their closest relatives, the Onychophora (velvet worms) and Arthropoda (invertebrates with articulated appendages), they represent a clade of legged ecdysozoans (molting animals) called Panarthropoda (Rota‐Stabelli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hox genes are prone to gains (15-17) and losses (18)(19)(20)(21), and their arrangement in a cluster can be interrupted, or even completely disintegrated (22)(23)(24)(25). Furthermore, the collinear character of the Hox gene expression can fade temporally (24,26,27) and/or spatially (28).…”
mentioning
confidence: 99%
“…Water bears’ compact bodies appear to have arisen by loss of a large part of an ancestral body plan, corresponding to the entire thorax and nearly the entire abdomen of Drosophila . This work revealed that animal body plans can arise by loss of a large body part, and a far larger part than we had anticipated [251]. How the finer, essential details of water bear anatomy first evolved and later diversified is not yet known.…”
Section: Water Bears: Evolution Of Body Forms and Survival Of Extremesmentioning
confidence: 98%
“…Postdoc Frank Smith, who had developed in situ hybridization methods for water bears, has sought to understand how the compact body plan of water bears arose long ago, back when the major groups of animals had diverged. Frank found that the Hox genes that define the head segments of arthropods are expressed in the same anterior-to-posterior register in water bears—but throughout almost their entire body—leading the animals to be called at times “walking heads” [251, 252]. Water bears’ compact bodies appear to have arisen by loss of a large part of an ancestral body plan, corresponding to the entire thorax and nearly the entire abdomen of Drosophila .…”
Section: Water Bears: Evolution Of Body Forms and Survival Of Extremesmentioning
confidence: 99%